Africanist Ethnomusicology and Musical Iconography: a dialogue with travelogues and music theory - (:unkn) unknown (My University, 2022)
Within the framework of a programme supported by the Agence Nationale de la Re-cherche on the harps of Central Africa, a collaboration between ethnomusicologists and iconographers of Western music was established around the musical iconography contained in travellers' accounts in the 19th century. A wider exploration has led to the interest in older sources which will be presented in this paper. Our work does not consist so much in the study of instrumental records as in the study of the representation of musical scenes in their context, as well as of the "figures" of musicians.Our paper will be based mainly on the Description historique des trois roy-aumes... by Giovanni Antonio Cavazzi (1687) and his collaborators, on the use made of it later, notably by Filippo Bonanni in his Gabinetto armonico (1722), and on ethnomusicological knowledge of the documented musical practices and their inser-tion in their society. Based on works in African history and ethnology, we will try to better identify the authors of the stories. We will be interested in the dialectic between text and image in order to understand the genesis of the plates, the intervention of the drawers, en-gravers and publishers.For Cavazzi's account, we will give an account of its reception through its var-ious versions and translations and their illustrations, in particular how they are con-ceived, realised, and even modified according to the editions. We will also discuss the use of some of his illustrations in later Western musical treatises, which some-times reveal organological misunderstandings due to a mistaken understanding of the musical practices initially observed.Taking into account the historiographic work on the authors of the stories, the rele-vance of their observations for today's ethnologist on ancient practices, whether they have disappeared, been modified or maintained, will be assessed. Finally, current field observations in Central Africa can shed light on these ancient
Keywords: African Research